The Endotracheal Suctioning and Oxygen Saturation in an Intensive Care Patient with Ischemic Stroke and Decreased Consciousness: A Descriptive Case Study - Lisnawati Lisnawati; Lisbet Octovia Manalu; Istianah Istianah; Budi Rustandi (STIKep PPNI Jawa Barat, 2026)
Background: Patients with ischemic stroke and decreased consciousness are at high risk of ineffective airway clearance due to impaired cough reflex and accumulation of airway secretions. This condition may lead to hypoxemia and further neurological deterioration, requiring appropriate airway management in intensive care settings. Objective: To describe the implementation of endotracheal suctioning as part of nursing care in an intensive care patient with ischemic stroke and decreased consciousness, with particular attention to oxygen saturation and clinical airway status. Methods: A descriptive single-patient case study was conducted in the general intensive care unit. Data were collected through direct observation, physical examination, bedside monitoring, and medical record review. The nursing care process included assessment, diagnosis, planning, implementation, and evaluation. Endotracheal suctioning was performed according to clinical indications and unit protocol, and oxygen saturation was observed before and after suctioning over a five-day period. Results: At baseline, the patient presented with decreased consciousness, retained airway secretions, bilateral rhonchi, weak cough reflex, tachypnea, and oxygen saturation of 92%. Across the five-day observation period, suctioning was followed by short-term improvement in oxygen saturation, with post-procedure values reaching 97–98%, accompanied by reduced secretion burden and clearer breath sounds. By the end of observation, respiratory status was more stable and suctioning was required less frequently. Conclusion: In this case, endotracheal suctioning performed on the basis of clinical indications was associated with improvement in short-term oxygen saturation and airway clearance indicators. These observations should be interpreted within the broader context of comprehensive intensive care and should not be taken as evidence of independent treatment effect. Further studies with stronger designs are needed to evaluate the contribution of suctioning in neurocritical patients